Modulation of macrophage activation marker induced by recombinant Mycobacterium smegmatis expressing Antigen-85B - Nur Ayuni, Kadir; Maria, E Sarmiento; Armando, Acosta; Norazmi, Mohd-Nor (2019)
Tuberculosis (TB) remains a major worldwide health problem which causes more than 1.3 million deaths annually. The development of a new vaccine as a replacement of Bacille Calmette Guerin (BCG) or to improve its efficacy is one of the goals mooted by the World Health Organization (WHO) to control TB. Mycobacterium smegmatis (M. smegmatis) is nonpathogenic and commensal in humans, which shares many characteristics with Mycobacterium tuberculosis (M. tuberculosis). Mycobacterial vectors including M. smegmatis have been successfully used in the development of experimental vaccines against TB